The millipede order Chordeumatida (Diplopoda) in Kazakhstan, with descriptions of three new species - Mikhaljova, Elena V.; Burkitbaeva, Ulzhan D.; Tuf, Ivan H.; Ulykpan, Kaman (Zootaxa, 2013)
The order Chordeumatida is represented in Kazakhstan by five species in three genera and three families. All species are recorded in the Altai and Dzhungarskii Alatau Mountains. Three species are described here as new to science: Altajosoma arshaty sp. nov., Altajosoma bukhtarma sp. nov. and Tarbagataya zaisanica sp. nov. The family Diplomaragnidae and the genus Altajosoma Gulička, 1972 are formally new to the fauna of Kazakhstan. Diagnosis of the genus Tarbagataya has been supplemented. All currently known Chordeumatida from Kazakhstan are keyed, including the new species. The distributions of all Kazakhstan chordeumatidan species are mapped.